2001
DOI: 10.1063/1.1360197
|View full text |Cite
|
Sign up to set email alerts
|

Structure and electronic properties of carbon onions

Abstract: Spherical and polyhedral carbon onions prepared from diamond nanoparticles are investigated by high-resolution transmission electron microscopy (HRTEM), Raman spectroscopy, and electron spin resonance (ESR). HRTEM and Raman studies show that, as a result of thermal annealing, diamond nanoparticles are transformed into spherical onions, and finally into polyhedral onions by the progress of graphitization. ESR spectra for spherical onions show only a narrow signal corresponding to dangling bond spins associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
115
2
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 215 publications
(123 citation statements)
references
References 34 publications
5
115
2
1
Order By: Relevance
“…30 OLC also demonstrates high selectivity and catalytic activity in the oxidative dehydrogenation of ethyl benzene to styrene. 31 The properties of OLC produced by annealing ND have been investigated by x-ray emission spectroscopy, 32 Raman spectroscopy, 33 electron energy-loss spectroscopy, 34 electron-spin resonance, 35 x-ray diffraction, 36 and ultraviolet-visible absorption spectroscopy. 37 A photoemission study of potassium intercalated polygonal hollow onions produced at 2140 K showed that these carbon onions behave as small graphite crystals and hence display bulklike rather than molecularlike behavior.…”
Section: Introductionmentioning
confidence: 99%
“…30 OLC also demonstrates high selectivity and catalytic activity in the oxidative dehydrogenation of ethyl benzene to styrene. 31 The properties of OLC produced by annealing ND have been investigated by x-ray emission spectroscopy, 32 Raman spectroscopy, 33 electron energy-loss spectroscopy, 34 electron-spin resonance, 35 x-ray diffraction, 36 and ultraviolet-visible absorption spectroscopy. 37 A photoemission study of potassium intercalated polygonal hollow onions produced at 2140 K showed that these carbon onions behave as small graphite crystals and hence display bulklike rather than molecularlike behavior.…”
Section: Introductionmentioning
confidence: 99%
“…19 Saturation may occur at this point, or occupation of higher molecular orbitals may occur, as observed in C 60 and the higher fullerenes at large akali to fullerene ratios. Several studies have been performed on onionlike carbon ͑OLC͒: high-resolution transmission electron microscopy ͑HRTEM͒, 16,17,22 Raman spectroscopy, 23 x-ray photoelectron spectroscopy ͑XPS͒, 24 electron energy-loss spectroscopy ͑EELS͒, 25 and electron-spin resonance ͑ESR͒. 2,25 Prior to this work the onionlike carbon valence band has been studied by x-ray emission spectroscopy but no intercalation of these particles has been performed.…”
mentioning
confidence: 99%
“…Spherical onions about 5 nm in diameter are seen. An electron spin resonance study indicated that the graphitic shells of the spherical onions contain a number of structural defects with dangling bonds (Tomita et al 2001). Oktrub et al (2001) also pointed out the presence of such defects in spherical onions on the basis of information derived from X-ray emission spectroscopy and quantumchemical calculation.…”
Section: Defective Spherical Onion Modelmentioning
confidence: 99%
“…Thus far, we have prepared carbon onions with diamond cores by heat treatment of diamond nanoparticles and have studied their electronic and optical properties (Tomita et al 2001(Tomita et al , 2002. Based on laboratory experiments and subsequent theoretical considerations, we have suggested that the optical extinction properties of the onions can be explained by a newly constructed ''defective'' spherical onion model.…”
Section: Introductionmentioning
confidence: 99%